A Fuzzy Linguistic Approach of Preventive Maintenance Scheduling Cost Optimisation - Oke, S.A.; Charles-Owaba, O.E. (Kathmandu University Journal of Science, Engineering and Technology, 2007)
The simultaneous scheduling of resource-constrained maintenance and operations is an emerging theory that is attracting the attention of both researchers and practitioners. The purpose of this paper is to capture the uncertainty in the development of a model that schedules both preventive maintenance and operational activities. Fuzzy logic is employed to transform the human expertise into IF-THEN rules. The approach has the advantage of revealing semantic uncertainty with the associated non-specifying measures. The methodology applied tracks the error values in terms of results in linguistic variable. The result obtained indicates the feasibility of tracking the uncertain measures in the model discussed. Thus, the study may be applicable to both production system and transportation organizations that are engaged in both maintenance and operational activities. The research has serious implication in terms of the ability to monitor the imprecision that were introduced in the previous models. This obviously provides a more reliable framework for researchers and practitioners interested in maintenance scheduling operation. The paper is new in that, it demonstrates the application of fuzzy logic in a form that was never documented.